Price Analysis of Dendrobium Orchid Flowers: Study on Orchid Entrepreneurs in Surabaya - Wanto, Hary (Research Horizon, 2021)
The economic crisis that caused many companies to close, but on the other hand that the agricultural sector is able to survive when the crisis occurs, the factor from within the orchid is the genetic factor or type of orchid, including natural or cruciferous orchids. If the type of natural orchid then the growth and flowering will be relatively very long if without special treatment, but if the type of orchid cruciferous like Dendrobium then the growth and flowering is relatively faster. To know the production elasticity of Dendrobium orchids of various age ranges in Kayoon Market, Surabaya City is technically efficient. To know the production and price of Dendrobium Orchid Flower in various age range in Kayoon Market, Surabaya City. As information for Orchid Flower entrepreneurs in overcoming problems in problems in orchid business. Orchids belong to the orchid tribe or family "Orchidaceae" which in Greek, the word "orchid" comes from orchis which means testicle or testicles. In ancient times orchids were identical to men, both in color, shape and even structure. This research uses independent variables that the research location will be determined at Orchid Flower entrepreneurs in Kayoon Surabaya City, with the consideration that Kayoon Flower Market is the center of ornamental plant entrepreneurs including Orchid Flowers in Surabaya City. The method used in determining the research location is purposive method. Multiple Linear Regression Method To test the hypothesis, first statistical analysis was conducted by using exponential method. the analysis result shows that orchid entrepreneurs in Surabaya have achieved technical efficiency in their business. However, some factors such as land area seem to have a significant influence on production, while other factors such as fertilizer may require further handling. In addition, the break-even point cost analysis identifies the production point at which entrepreneurs can break even, which is important for the sustainability and success of the orchid business in the local market.